Eddy current technique as a nondestructive method for evaluating the degree of sensitization of 304 stainless steel. (15th August 2020) - Kelidari, Yeganeh; Kashefi, Mehrdad; Mirjalili, Mostafa; Seyedi, Mahla; Krause, Thomas W.
Highlights: Using DL-EPR to evaluate %DOS of 304 SS sensitized in different conditions. Characterizing the microstructure of sensitized samples. Using eddy current technique to establish the relation between %DOS and ECT results. Developing the equation of % DOS  = 2×10 -5 (EC Voltage) 2  −0.1031 ( EC Voltage ) + 120.95. Developing the equation of % DOS  = 178.48 ( N.I. ) + 177.01 between impedance and %DOS. Abstract: The application of eddy current (EC) technique in detection of sensitization before the occurrence of intergranular corrosion was investigated. For this purpose, EC experiments were performed on 304 stainless-steels sensitized at 650 °C and 750 °C for 1–20 hours. The double-loop electrochemical potentiodynamic reactivation (DL-EPR) and microstructural investigations were also carried out to evaluate the degree of sensitization (DOS). The DL-EPR results showed that the maximum sensitivity occurred within 4 h at 650 °C. The EC results indicated a reduction in voltage and impedance with increasing DOS. Finally, empirical relationships between DL-EPR and EC test results were developed.